Políticas públicas de lazer no município de Castanhal: um estudo sobre o Apeú - FERREIRA, Emerson Maciel (2019)
The present work entitled "Public Policies of Leisure in the Municipality of Castanhal: A Study on the Village of Apeú" starts from the perspective that the right to the city becomes necessary and must be understood in a broad way, seeking to reflect on the current social model that many denies this space to citizens and constitutes the alienated use of spaces, masking the true ways of enjoying it. The study had as general objective to answer how the public policy of leisure in the municipality of Castanhal has been configured and as specific objectives: to analyze leisure policies in Vila do Apeú; the existence or not of these policies in the Bay of Apeú, in order to establish relations between scientific studies on leisure and state action in the implementation of public policies in the city. Thus, this work, which has a theoretical-methodological foundation in the perspective of dialectical historical materialism, involved studies on the Vila do Apeú, as well as documentary researches that characterize the organization of the city of Castanhal. He also had an interview using a semi-structured script, recorded with the current municipal secretary of sports and leisure. The results of the study showed that the Vila do Apeú is not very safe for the golden days of usufruct of the Rio Apeú as a leisure space in the municipality. Currently there is no leisure policy being implemented specifically in the area of the Apeú border. It is considered the possibility of implementation of some projects in the area, if a possible restructuring that is planned to space, in fact happens.